Survei Ketersediaan dan Kelayakan Sarana dan Prasarana Penjasorkes di SMA Negeri se-Kabupaten Purworejo (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the availability and feasibility of facilities and infrastructure in public high schools in Purworejo Regency. In this study using a method approach mixed, the subjects in this study were Physical Education teachers at SMA Negeri Purworejo, namely 11 teachers. The data was obtained from the process of questionnaires, interviews, observations, and documentation. Then the data analysis technique using descriptive percentage and data reduction techniques. This study obtained results from physical education teachers in the form of: for the availability of facilities and infrastructure for SMA Negeri Purworejo, the category was very good with a percentage of 74.17%, sufficient category 8.88% and less category 16.94%. Then in terms of feasibility, the facility and infrastructure in each school are very decent, not damaged, far from danger, etc. The conclusion from this research is that the overall availability and feasibility of facilities and infrastructure in Purworejo Regency is very good and very feasible. Suggestions for Physical Education teachers to maintain and maximize existing facilities and infrastructure for better learning